Advanced Degrees in Academic Colorectal Surgery - Hall, Jason F. (Clinics in Colon and Rectal Surgery, 2013)
Because of the increasing complexity of medical care, growing numbers of physicians are supplementing their medical education with additional training in basic research, public health, and leadership/business. The doctor of philosophy, master of public health, and master of business administration are popular degrees that give matriculants added levels of knowledge and expertise in their respective fields. This article reviews the relative advantages and disadvantages of each degree as they relate to a career in surgery. Data regarding the academic and financial outcomes of students obtaining these degrees are reviewed.
Keywords: doctor of philosophy; master of public health; master of business administration; surgery; colorectal surgery; advanced degrees